Про систему криміналістичної тактики та короткий аналіз її складових - Когутич, І.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
На основании современного воззрения на предмет криминалистики предложен и рассмотрен один из вариантов системы криминалистики. Осуществлён краткий анализ её составных частей: следственной и судебной тактики, тактики преступной деятельности и поисково-розыскной тактики. One of variants of the improved system of criminalistics was offered and considered in the article on the basis of modern view for the subject of criminalistics. A brief analysis of its constituent parts: the investigative and judicial tactics, the tactics of criminal activity and search-tracing tactics was conducted.